Studies on the stereoselective synthesis and immunosuppressive activity of dihydroartemisinin-O-glycoside derivatives. Issue 16 (15th August 2020) - Yu, Yu; Yu, Jingfeng; Zou, Xiaosu; Xu, Wei; Zhang, Jinghua; Bian, Hongzhu; Dong, Xun; Shen, Zhengwu
Graphical abstract: Abstract: Eight new dihydroartemisinin-O-glycosides were synthesized with their relative configurations were determined based on NMR spectrum. In vitro immunosuppressive assay showed that 10α-dihydroartemisinin-β-O-d -mannoside (19a) demonstrate 88% inhibition towards T cells proliferation and 98% reduction in IFN-γ levels in cell media. These results suggest that dihydroartemisinin-O-glycoside as a potential lead for further in vivo evaluation.